Analysis of the behavior of asynchronous electric drive with a closed scalar control system when changing the inductance of the magnetizing circuit - Yu. L. Zhukovskiy; B. Y. Vasilev; N. A. Korolev; Y. M. Malkova (Universitas Pendidikan Indonesia, 2023)
The article was devoted to the study of an automated electric drive with a scalar closed-loop speed control system. Severe duty and operating modes of electric drive determine the actual service life. Wear of the induction motor, as a key link of the electric drive, was associated with deviation from nominal parameters. The deviation of parameters of the induction motor equivalent circuit determined the resultant change of characteristics. The parameters of the equivalent circuit determined the accuracy of the adjustment of regulators and optimal algorithms in the control system of the electric drive. In continuous operation modes the possibility of auto-tuning regulators, which requires stopping or no-load mode, was excluded. The paper considered the influence of the magnetization circuit mutual inductance value of the induction motor on the behavior of the electric drive control system. Evaluation of the behavior of the scalar closed-loop speed control system was performed on the basic energy (power factor, efficiency factor) and mechanical (speed, electromagnetic torque) characteristics of the electric drive.